Evaluating possible spectroscopic variation of Bennu's sampling site. Issue 1 (19th October 2022) - Praet, A; Poggiali, G; Barucci, M A; Clark, B E; Zou, X-D; Simon, A A; Kaplan, H H; Li, J-Y; Alcaria, C
ABSTRACT: The OSIRIS-REx spacecraft completed the first part of the primary objective by successfully sampling the surface of asteroid (101955) Bennu and storing the acquired sample in the re-entry capsule. The sampling 'Touch-And-Go' (TAG) maneuver was performed nominally at the primary sampling site, Nightingale, in Bennu's Northern hemisphere. As a consequence of the TAG, material at the sampling site was mobilized and the morphology of the area was altered. This event offered a unique opportunity to investigate, in detail, the subsurface of asteroid Bennu giving access to fine grained and less altered material from Nightingale crater. We performed a detailed study on the infrared spectrum in the Nightingale region to search for modification resulting from the sampling event by analysing different features: slope, the H2 O–OH − related absorption band in the 2.7 μ m region, and other possible features. Our results show that, despite visible alteration of the TAG location detected by cameras, no strong variations are observed in the near-infrared bands and their quantitative evaluation is not possible beyond all the instrumental effects, although some changes may have occurred. We confirm that the infrared spectrum of the sampling site becomes redder with respect to the pre-TAG observations, conceivably due to fine material mobilization and exposure of less altered material, as confirmed by decreased spectral convexity. We identify possible modification of hydrated band at 2.7 μ m but with some concerns due to data quality. However, our results place new constraints on the nature of Bennu's subsurface material and the sample collected by OSIRIS-REx.